Proses Pengisian Jabatan dan Upaya Menciptakan Aparatur Pemerintah yang Profesional, Efektif dan Efisien pada Dinas Pendidikan Provinsi Sumatera Barat - susiyanti meilina (LPPM STISIP IMAM BONJOL, 2023)
Research has been conducted at the West Sumatra Provincial Education Office on the process of filling positions and efforts to create a professional, effective and efficient government apparatus.